The perforations in healthy intestines: stress piercing, called "spontaneous" - Latourrette, Federico (Cirugía del Uruguay, 2020)
1) Three new cases of rupture of the normal intestine wall produced by musculr violence are presented. Review of the worlds literature about this subject that now amounts to 70 cases. 2) Definition. 3) Pathophysiology, symptomatology and pathology. Different winds of muscular violence that produced them. The predisponent role of the hernias. 4) Management of the intestinal perforation.